Influence of an iron dextran injection in various diseases on hematological blood parameters, including serum ferritin, neonatal dairy calves - Sickinger, Marlene; Joerling, Jessica; Büttner, Kathrin; Roth, Joachim; Wehrend, Axel; Justus Liebig University Giessen (My University, 2024)
Background: Feeding milk substitutes with low iron content or whole milk without iron supplementation is considered a major factor in developing iron-deficiency anemia in neonatal dairy calves. Young calves are often supplemented with iron dextran injections on the first day of life to prevent anemia. However, the effects of preventive treatment and the presence of disease on serum iron (Fe) concentrations, serum ferritin levels, and hematological blood parameters during the early neonatal stages have not been examined in detail. Therefore, we examined and evaluated the effects of iron dextran injections and health status on the development of hematocrit (Ht), red blood cells (RBC), hemoglobin concentration (Hb), erythrocyte indices (mean corpuscular volume, mean corpuscular hemoglobin, mean corpuscular hemoglobin concentration), Fe, and serum ferritin concentrations in dairy calves within the first 10 days of life. The suitability of serum ferritin as a reliable indicator of anemia in very young calves was evaluated by correlating ferritin concentrations with known laboratory diagnostic parameters of anemia. Results: Iron supplementation significantly increased Fe levels (P = 0.048) but did not affect serum ferritin levels in neonatal calves. Fe concentrations were significantly lower in diseased than healthy calves (P = 0.0417). Iron supplementation significantly affected the health status, as observed in Ht (Ptreat=0.0057; Phealth=0.0097), RBC (Ptreat=0.0342; Phealth=0.0243), and Hb (Ptreat=0.0170; Phealth=0.0168). Serum ferritin levels did not significantly correlate with Fe levels. Both groups showed marked differences in ferritin levels, with the highest levels measured on day 2. Fe concentrations showed weak negative correlations with Hb and Ht levels on day 3 (ρ=-0.45; P = 0.0034 and ρ=-0.045; P = 0.0032, respectively). RBC count showed strong positive correlations with Hb and Ht levels (ρ = 0.91 and ρ = 0.93; P < 0.001). Conclusion: Iron dextran injections increased Fe concentrations but reduced Ht level, RBC count, and Hb level. The presence of diseases led to a reduction in Fe and higher values of Ht, RBC, and Hb in moderate disease than in severe disease. Due to physiological fluctuations during the first 3 days of life, serum ferritin level seems unuseful for evaluating iron storage before day 4 of life.
Keywords: ddc:630